PARADIGMA BARU HUKUMAN MATI: ANALISIS SUBSTANTIF KUHP DAN KUHP NASIONAL - Balya, Humam (Gapenas Publisher, 2025)
The death penalty is one of the principal forms of punishment that has long been implemented in the Indonesian criminal justice system. The increasing number of criminal offenses each year in Indonesia is one of the reasons behind the government's initiative to reform the Indonesian Criminal Code (KUHP). One of the key issues in the new KUHP Nasional (National Criminal Code) is the reformulation of death penalty provisions, which allows for the postponement of execution in cases where the convict demonstrates significant behavioral improvement. This study aims to (1) analyze the substantive regulation of the death penalty in the KUHP and the new KUHP Nasional; and (2) compare the normative approaches to the death penalty in both legal frameworks. The research employs a normative legal research method and utilizes primary legal sources in the form of statutory regulations. The findings show that the KUHP treats the death penalty as a principal punishment without providing any alternative mechanisms, while the KUHP Nasional introduces a new, more humanistic paradigm that allows for conditional abolition based on the rehabilitation of the convict’s behavior.